Magnetic interactions and dielectric dispersion in Mg substituted M-type Sr-Cu hexaferrite nanoparticles prepared using one step solvent free synthesis technique. Issue 4 (March 2018) - Nandotaria, Reshma A.; Jotania, Rajshree B.; Sandhu, Charanjeet Singh; Hashim, Mohd.; Meena, Sher Singh; Bhatt, Pramod; Shirsath, Sagar E.
Abstract: In this study, we report the effect of Mg-substitution on structural, magnetic and dielectric properties of M-type Sr-Cu hexaferrites (Sr0.5 Cu0.5−x Mgx Fe12 O19, x = 0.0, 0.1, 0.2, 0.3, 0.4 and 0.5) prepared by using one step solvent free synthesis technique. Rietveld refinement of X-ray diffraction (XRD) patterns has confirmed the formation of M-type hexaferrite phase. The crystallite size was estimated from XRD lies within the nanometer range. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were also employed to estimate the particle size. TEM micrographs of pure and substituted samples show hexagonal structure with an agglomeration is noticed for x = 0.5. Magnetic interactions were studied by vibrating sample magnetometer (VSM) and Mössbauer spectroscopy technique. VSM results reveal that the values of saturation magnetization ( M S ) increases initially for x = 0.2 Mg-substitution after that decreases drastically from 47.15 emu/g ( x = 0.2) to 1.66 emu/g ( x = 0.5). Similar trend was also observed for remanent magnetization ( M r ) and found to decrease from 17.5 emu/g ( x = 0.2) to 0.3 ( x = 0.5) emu/g. Similarly, the higher value of coercivity ( H C = 1995 Oe) was observed for x = 0.2 sample. Room temperature Mössbauer spectra (MS) were recorded to probe magnetic properties at microscopic level. Five sextets were observed for each sub-lattice. Iron ions were found in Fe 3+ high spin state. The dielectric constant of all samples found to be decreased with increase in the frequency. The dielectric dispersion behaviour was well explained in terms of Maxwell-Wagner polarization in accordance with the Koop's phenomenological theory.